Indirekta effekter på marklavars abundans och diversitet vid ökad kvävehalt i marken - Svanlund, Sara; Wahlgren, Emmelie (2013)
Lichens are adapted to bright and sparse forests on oligotrophic ground. Due to a slow growth rate and high light demand lichens will suffer from competition in eutrophic environments. Therefore, lichens have disappeared from managed forests where the forest industry has increased the productivity. A reduced abundance of lichens will affect both biodiversity of the forest and the reindeer winter graze lands. It is important to understand how and for how long fertilization affects the abundance and diversity of lichens in order to protect lichen rich ecosystems. We have registered the biomass and number of lichen species in eight plots (four nitrogen rich and four nitrogen deficient) and compared fertilized Sami settlements with their oligotrophic surroundings in the nature reserves of Tjeggelvas. We have assumed that all plots initially had the same nutritional status and that a supply of organic leavings fertilized the settlements more than hundred years ago. The results indicate a long lasting (>100 years) decrease in both number of lichen species and amount of biomass with increased levels of nitrogen in the humus layer. We also found a significant correlation between field vegetation (mostly Vaccinium vitis-ideae) and lichen abundance and diversity. Betula pendula was the only tree species affecting the abundance and diversity of lichens and no significant connection with soil nitrogen was found. Individual lichen species differed in nitrogen tolerance, with Cladina rangiferina and Cladina arbuscula being more widely abundant than for example Stereocaulon spp. A small set of data, restricted to eight plots, makes statistical calculations doubtful but the results are consistent with established studies. Lavar är anpassade till öppna och ljusa skogar på näringsfattig mark. I miljöer med mycket näring konkurreras de ut på grund av sin långsamma tillväxt och ett stort ljusbehov. Det har lett till att lavar missgynnats av många produktionshöjande skogsskötselåtgärder. Den biologiska mångfalden och ...